134 Communication with palliative care patients about driving and opioids. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Collins, Emma; Jones, Andrew
Abstract : Background: Recent changes in the law regarding liability and driving offences whilst on opioids, highlighted by the MHRA, reinforces the importance of communication about driving whilst taking medication and the law. A robust approach to communicating and documenting this information is required. Methods: The audit standard was NICE CG140: 'Opioids in palliative care: safe and effective prescribing of strong opioids for pain in palliative care of adults'. Patients seen in January 2015 in outpatients, day unit, inpatients and the community initiated on opioids or had dose titration, were reviewed. Cases were excluded if had an ECOG of 3–4. The data was analysed and presented at our clinical governance meeting. This triggered a redesign of our inpatient admission proforma. The method of documenting driving status on electronic patient records was changed and promoted. Driving safety leaflets were made available. The audit cycle was completed in June 2017. Results: Pre-implementation, 33 cases were included in analysis. 9% of cases had their driving status documented. 0% had documentation of discussion of side effects and 9% documented that the patient was informed about the consequences of driving on opioids. On re-audit, 20 cases were analysed. Driving status was documented in 50% of cases, 30% showed discussion of side effects, and 30% documented consequences of driving on opioids. Conclusions: It is the clinician's responsibility to appropriately counsel patients on risks of driving whilst taking medications, to provide 'medical defence'. Although conversations often occur, they are seldom documented and can therefore not be evidenced. Having written information to offer can provide evidence, but is no substitute for thorough conversation and eliciting comprehension. In our department, more needs to be done to educate the SPCT to ensure this is done routinely as part of the first assessment, and reviewed frequently, with changes to medications being a prompt.